ANALISIS ANTIOKSIDAN EKSTRAK DAUN NANGKA (Artocarpus heteropyllus L ) DENGAN MENGGUNAKAN METODE FRAP - sulasmi, sulasmi (Jurnal Penelitian Farmasi Dan Herbal, 2024)
Background: Antioxidants are compounds that are able to counteract or reduce the negative effects of oxidants in the body. The activity of antioxidants is the ability of jackfruit leaves to ward off free radicals. Jackfruit leaf (Artocarpus heteropyllus L.) belongs to the Moraceae family which contains secondary metabolites. The results showed that jackfruit leaves are used as natural antioxidants because they contain secondary metabolites, namely flavonoids, saponins and tannins. Purpose : of this study was to determine the level of antioxidant activity of jackfruit leaf extract using ferric chloride reagent using Ultraviolet-Visible (Uv-Vis) spectrophotometry. Methods : This study used an experimental method, simplicia was extracted by maceration using 96% ethanol and the filtrate obtained was evaporated with the help of a rotary evaporator. Jackfruit leaf extract was analyzed for antioxidant activity with ferric chloride reagent using UV-Vis spectrophotometry in the range of 400 nm-800 nm. Results : of phytochemical screening of jackfruit simplicia powder obtained flavonoid compounds, saponins and tannins. The of the determination of antioxidant levels of ascorbic acid at a wavelength of 236 nm with levels of 87.4712 mgQE/g and levels of jackfruit leaves at a wavelength of 400 nm with levels of 1.2736 mg AAE/g. Conclusion : The results showed that the IC50 value of jackfruit leaves had a value of 74.6 ppm.